Intrafraction target shift comparison using two breath-hold systems in lung stereotactic body radiotherapy - Alejandro Prado; Daniel Zucca; Miguel Ángel De la Casa; Jaime Martí; Leyre Alonso; Paz García de Acilu; Juan García; Ovidio Hernando; Pedro Fernández-Letón; Carmen Rubio (Physics and Imaging in Radiation Oncology, 2022)
Background and purpose: In lung Stereotactic Body Radiotherapy (SBRT) respiratory management is used to reduce target motion due to respiration. This study aimed (1) to estimate intrafraction shifts through a Cone Beam Computed Tomography (CBCT) acquired during the first treatment arc when deep inspiration breath-hold (DIBH) was performed using spirometry-based (SB) or surface-guidance (SG) systems and (2) to analyze the obtained results depending on lesion localization. Material and methods: A sample of 157 patients with 243 lesions was analyzed. A total of 860 and 410 fractions were treated using SB and SG. Averaged intrafraction shifts were estimated by the offsets obtained when registering a CBCT acquired during the first treatment arc with the planning CT. Offsets were recorded in superior-inferior (SI), left–right (LR) and anterior-posterior (AP). Significance tests were applied to account for differences in average offsets and variances between DIBH systems. Systematic and random errors were computed. Results: Average offset moduli were 2.4 ± 2.2 mm and 3.5 ± 2.6 mm for SB and SG treatments (p < 0.001). When comparing SB and SG offset distributions in each direction no differences were found in average values (p > 0.3). However, variances were statistically smaller for SB than for SG (p < 0.001). The number of vector moduli offsets greater than 5 mm was 2.1 times higher for SG. Compared to other locations, lower lobe lesions moduli were at least 2.3 times higher. Conclusions: Both systems were accuracy-equivalent but not precision-equivalent systems. Furthermore, the SB system was more precise than the SG one. Despite DIBH, patients with lower lobe lesions had larger offsets than superior lobe ones, mainly in SI.